OS 27-01 IS HYPERTENSION A RISK FACTOR FOR RECURRENCE AFTER RADIOFREQUENCY CATHETER ABLATION IN ATRIAL FIBRILLATION?. (September 2016) - Kim, Mi-Na; Cho, Donghyuk; Shim, Jae-Min; Choi, Jong Il; Park, Seong-Mi; Kim, Young-Hoon; Shim, Wan-Joo
Abstract : Objective: Hypertension (HT) is the important risk factor for atrial fibrillation (AF). Hemodynamic overload by increased blood pressure causes atrial wall stretch and atrial dysfunction. Left atrial (LA) dysfunction has been regarded as the most important risk factor for AF recurrence after radiofrequency catheter ablation (RFCA). But there are controversies regarding the role of hypertension as a risk factor of AF recurrence after RFCA. The aim of this study was to assess whether the hypertension is an independent risk factor for AF recurrence after RFCA. Design and Method: 130 patients with non-paroxysmal AF (88% male, 54.6 ± 9.3yr old) who had undergone RFCA were enrolled. The definition of recurrence was atrial tachycardia lasting over 30 seconds or the existence of AF in ECG or on 24 h ECG monitoring during follow up. LA function was assessed by LA diameter, LA volume index (LAVI), and LA emptying fraction (LAeF). We evaluated the relation between recurrence of AF and clinical factors or echocardiographic parameters. Results: Among 130 patients, 54 patients had hypertension, 8 patients had diabetes and 9 patients had the history of heart failure. During 2 years follow up, 61 patients (46.6%) experienced AF recurrence. By univariate analysis, age, the presence of hypertension, LAVI, LAeF and E/e' were related with AF recurrence (Odds ratio R = 1.03, 2.67, 1.03, 0.94 and 1.11, P = 0.015, 0.008, 0.029, 0.013 and 0.027). Among these parameters, age, LAVI and E/e' did not show statistical significance for predicting AF recurrence, by multivariate analysis. But both LA dysfunction and the presence of hypertension remained as independent risk factors for AF recurrence with odd ratio 0.95 (P = 0.041) and 2.30 (P = 0.028) respectively. Conclusions: In non-paroxysmal AF patients who had taken RFCA, the presence of HT was independently associated with AF recurrence. These findings suggest that upstream pathology caused by hypertension might be an important factor for maintaining sinus rhythm after RFCA of AF.